Development of the Person–Family Fit Construct: An Extension of Person–Environment Fit into the Family Domain - Padmasiri, M. K. Dinithi; Kailasapathy, Pavithra; Jayawardana, A. K. L. (SAGE Publications India Private Limited, 2019)
This article defines a person’s environment as a combination of work and family environments by extending the person–environment fit theory to include the family domain. The study extends the person–environment fit construct by including person–job fit, person–organization fit, person–group fit, person– supervisor fit (all in work environment) and person–family fit (family environment). In the two studies that were carried using operational-level employees from various industries, we empirically develop a scale for the new concept person–family fit, validated person–family fit scale and the person–environment fit construct. This study makes several theoretical contributions including defining person–family fit construct, developing a scale to measure the same and confirming its inclusion into the person–environment fit construct. Managerial implications are provided to ensure person–job fit, person–group fit, person–supervisor fit and person–family fit in the working environment.
Keywords: Person–environment fit theory, work/family border theory, scale development, person–family fit, work environment, family environment